Differentiation of cows' milk intolerance and gastro-oesophageal reflux. Issue 5 (November 1995) - Staiano, A; Troncone, R; Simeone, D; Mayer, M; Finelli, E; Cella, A; Auricchio, S
Abstract : The aim of this study was to compare a non-invasive test of small bowel permeability with a more invasive approach involving endoscopy, mucosal biopsy, and oesophageal pH monitoring for rapidly differentiating gastro-oesophageal reflux (GOR) and cows' milk intolerance in 25 infants with persistent vomiting. Each subject underwent a cellobiose/mannitol permeability study, upper gastrointestinal endoscopy with oesophageal and small bowel biopsies, and a 24 hour pH study. Reflux disease and/or cows' milk intolerance was responsible for vomiting in 24 (96%) of the subjects. Sixteen (64%) of the infants had GOR alone, four (16%) had GOR and cows' milk intolerance, and four (16%) had cows' milk intolerance alone. Morphometric analysis of small bowel biopsies was abnormal in 19% of the patients with GOR alone and in 67% with cows' milk intolerance with or without GOR. The permeability test was abnormal in only 6% of the patients with GOR but in 100% with GOR and cows' milk intolerance and in 100% with cows' milk intolerance alone. The non-invasive permeability study aimed at rapid determination of cows' milk intolerance should pre-empt a more invasive approach in the evaluation of infants with persistent vomiting.